2020
DOI: 10.1111/dth.13721
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of bullous pemphigoid in Chinese patients withTripterygium wilfordiiHook F

Abstract: Tripterygium wilfordii Hook F (TwHF) is a traditional Chinese herb used in many medicinal applications, but the treatment of bullous pemphigoid (BP) with TwHF has never been reported. The aim of this study was to evaluate the efficacy and safety of TwHF in BP patients. A retrospective study was performed from January 2015 to September 2019 in the Department of Dermatology, Peking Union Medical College Hospital. A total of 10 patients with mild to moderate BP and treated with TwHF were enrolled in the study wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Some reports have also found a temporal association between the use of herbal supplement intake and the onset of skin disease or flare-up of skin diseases [35,36]. On the other hand, the intake of low-dose Tripterygium wilfordii Hook F, a traditional Chinese herb, was shown to have anti-inflammatory effects in a small case series of patients with mild and moderate BP [37]. Therefore, the disclosure of CAM use by patients to their healthcare providers is important, especially in the case of phytotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have also found a temporal association between the use of herbal supplement intake and the onset of skin disease or flare-up of skin diseases [35,36]. On the other hand, the intake of low-dose Tripterygium wilfordii Hook F, a traditional Chinese herb, was shown to have anti-inflammatory effects in a small case series of patients with mild and moderate BP [37]. Therefore, the disclosure of CAM use by patients to their healthcare providers is important, especially in the case of phytotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Western medicine treatment, traditional Chinese medicine treatment is currently receiving increasing attention, and its efficacy is considerable. For example, Ge et al (27) discovered that Tripterygium wilfordii Hook F was safe and effective in treating mild to moderate BP, with much fewer adverse effects than hormone treatment. In this case, we chose berberine primarily based on traditional Chinese medicine's basic theory and syndrome differentiation for patients.…”
Section: Discussionmentioning
confidence: 99%
“…6 In China, Tripterygium wilfordii Hook F (TwHF) is widely used for treating autoimmune and inflammatory diseases such as BP due to its significant anti-inflammatory and immunosuppressive properties. 9,10 To achieve complete remission, BP patients usually need several years of treatment and adverse effects during treatment may lead to related complications or even death. 11 Recently, multiple studies have suggested that the structure and composition of the gut microbiota (GM) in various immune diseases patients exhibit significant alterations.…”
Section: Introductionmentioning
confidence: 99%